Contextualism of Mosque Architecture in the City: Case Study of the Abu Bakar Mosque in Bangsar - Kanesh, Kevin; Mohd Rasdi, Mohd Tajuddin; Mei Jean, Leow; al-Darahirst, Homam (Journal of Techno-Social, 2018)
This research identifies the issues related to the contextualism of mosque architecture towards its urban setting as well as how it translates into inclusivism into the social structure. The main aims of the research is to evaluate the architectural contextualism from the perspective of form and design against the backdrop of the urban fabric and evaluating the contextualism of social inclusivism in the mosque architecture from the perspective of the non-Muslim society participation with the Muslim society. A case study of the Abu Bakar Mosque in Bangsar, Kuala Lumpur was conducted via observation and interviews with the mosque management. The findings shows that through time the visionary management has turned the mosque in terms of its activities and design in context towards its urban setting as well as into inclusivism within the social structureÂ Â